Inovasi Pembelajaran Pendidikan Agama Islam Berbasis Problem Based Learning - Ikrima Mailani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Educators are very important in their efforts to achieve the desired learning goals in the activities of the teaching and learning process. While students act as subjects as well as objects in applying strategies, models and learning methods. Various ways can be done by the teacher/lecturer to be able to convey information to students (knowledge transfer), both in the form of learning related to teaching materials or insightful ones globally. The process of transferring knowledge with the classical/traditional method can no longer be maintained, because students who are expected by the community are intelligent students who are responsive to the development of the times, and not just as spectators and listeners. The breakthrough offered by observers of education is with a new concept, namely the Problem Based Learning (PBL) learning model, this learning model is not just a process of transferring knowledge from teacher to student, but students can do, try and reconstruct their own teaching materials based on problems existing in the educational environment. Changing the old paradigm that states that every problem must be avoided, but changing it into a new paradigm, that a problem must be faced and the solution sought as soon as possible, so also in the process of teaching and learning activities that give birth to effective, creative and innovative learning.